2020
DOI: 10.1021/acs.chemrev.0c00033
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Devices Using Open Framework Materials

Abstract: Open framework materials (OFM) constitute a large and growing class of nanoporous crystalline structures that is attracting considerable attention for electronic device applications. This review summarizes the most recent reports concerning electronic devices enabled by either of the two primary categories of OFM, metal−organic frameworks (MOFs) and covalent−organic frameworks (COFs). Devices in which the OFM plays an active role (as opposed to acting only as a selective sorbent or filter) are the principal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
199
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(206 citation statements)
references
References 540 publications
0
199
0
7
Order By: Relevance
“…19,20 In the recent years, it has been possible to preconceive OSC arrangements for a large variety of applications, including optoelectronics. [21][22][23][24][25][26] Originally developed for applications in gas storage and separation, MOF-based materials have found interest also with regard to other application elds, based on properties like large electrical conductivities 27 of the order of 10 3 S m À1 , room temperature charge carrier mobility 28 as large as 220 cm 2 V À1 s À1 , and other interesting properties like thermal activated delayed uorescence, 29 emphasizing the emergent nature of MOF-based optoelectronic materials. [30][31][32][33] In the present work, we demonstrate the potential of the MOF-based approach to create structurally-controlled 1D OSCs based on Pn.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In the recent years, it has been possible to preconceive OSC arrangements for a large variety of applications, including optoelectronics. [21][22][23][24][25][26] Originally developed for applications in gas storage and separation, MOF-based materials have found interest also with regard to other application elds, based on properties like large electrical conductivities 27 of the order of 10 3 S m À1 , room temperature charge carrier mobility 28 as large as 220 cm 2 V À1 s À1 , and other interesting properties like thermal activated delayed uorescence, 29 emphasizing the emergent nature of MOF-based optoelectronic materials. [30][31][32][33] In the present work, we demonstrate the potential of the MOF-based approach to create structurally-controlled 1D OSCs based on Pn.…”
Section: Introductionmentioning
confidence: 99%
“…Comprised of inorganic subunits, also known as secondary building units (SBUs), and organic linkers, MOFs assemble in crystalline three-dimensional structures with large surface areas and high porosity. 22 Because of their chemical diversity and tunability, MOFs have found a wide range of applications including, but not limited to, liquid and gas adsorption, [23][24][25][26] chemical separation, 27,28 catalysis, 29 chemical degradation, 30 and proton transport, 31 as well as in electronic devices 32 and magnets. 33 It has recently been shown that some MOFs display remarkable water capture capabilities under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The enormous chemical and structural diversity of ligands and metal ions provides researchers with a playground filled with infinite creative possibilities, allowing design of 2D c-MOFs. Although there are no commercial devices that yet incorporate 2D c-MOF materials, numerous proof-of-concept device demonstrations have appeared 5,6 . These advances are inspiring and demonstrate that 2D c-MOFs are an emergent class of layered electronic materials.…”
mentioning
confidence: 99%